Climate change as a challenge to the armed forces - Földi, László (Sodobni vojaški izzivi, 2022)
Threats to national security are becoming more and more diverse, and factors are emerging which we did not expect. In recent decades, we have increasingly perceived extreme environmental events resulting from climate change as threats. This includes natural disasters related to weather, climate and/or water (windstorms, extreme precipitation, heat waves and extreme cold, wildfires, droughts,.). Military forces are carrying out their operations while being more and more affected by difficult environmental circumstances, and in addition their use in disaster management has become indispensable in our times. In this paper, the authors examine climate-related disasters’ impact on national security and on the use of military forces.
Keywords: adaptation; Evropska unija; mitigation; NATO; Oborožene sile; Podnebne spremembe; prilagoditev; security; ublažitev; varnost